Health Related Quality of Life norm data of the Italian general population: results using the EQ-5D-3L and EQ-5D-5L instruments (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Many studies have been conducted in Italy to assess Health-Related Quality-of-Life (HRQoL) in subjects with different diseases. However, no recent HRQoL population norm data were available to make comparisons with diseased populations. We assessed HRQoL norm data using the generic instrument EQ-5D in its standard version (EQ-5D-3L) and with the recently introduced version (EQ-5D-5L).Methods: A survey was conducted on 6,800 individuals representative of the Lombardy general adult population for age, gender and geographical distribution. Each participant underwent a telephone interview with questions using the EQ-5D-3L and the EQ-5D-5L descriptive systems, the visual analogue scale (EQ-VAS) and socio-demographic data.Results: participants were 48% male, aged on average 51.9 years. With the 3L version, men and women aged 18-35 years reporting a full health state were 71.3% and 56.5%, respectively, those aged >76 years decreased to 29.5% and 13.5%, respectively. The proportion of respondents reporting no problems decreased with the 5L version. The mean (standard deviation) of the EQ-VAS was 87.7(12.1) and 85.0(15.2) among men and women aged 18-35 years, and 68.0(20.6) and 64.4(23.2) in men and women aged >76 years. The mean (standard deviation) utility obtained from the 3L version ranged from 0.965(0.068) and 0.944(0.086) among men and women aged 18-35 years, to 0.880(0.123) and 0.829(0.137) in men and women aged >76 years. Similar results were obtained with the 5L version.Conclusion: HRQoL norm data are now available from the Italian general adult population, to be used as a reference in clinical sector, economic evaluations and in policy setting.